Evaluation of Bacillus subtilis biopreparations as growth promoters in chickens - Mili?n, Grethel; Rond?n, A. J.; P?rez, M.; Bocourt, Ram?n; Rodr?guez, Zoraya; Ranilla, M. J.; Rodr?guez, M.; Carro, M. D. (Cuban Journal of Agricultural Science, 2013)
Bacillus subtilis bioprepations were evaluated as growth promoters in chickens. Two hundred chickens of the Cuban breeder hybrid EB34 were used, according to a completely randomized design. Four treatments were studied: diet (maize-soybean), diet + biopreparation C-31, diet + biopreparation C-34 and diet + biopreparation E-44, applied to a dosage of 109 endospores/g-1 of concentrate. The experiment was carried out for 42 d and microbiological and fermentative indicators were assessed. The study of these biopreparations provoked improvements in the microbial balance of the birds? caecum, when at 21 and 42 d was observed increase of the population of Lactobacillus, Bacillus endospores and total anaerobes, as well as reduction of coliforms at 42 d. In the treated groups with the B. subtilis biopreparations and their endospores the total and individual short chain fatty acids (SCFA) and the lactic acid content, were increased with a decrease of the intestinal pH at 42 d. It is concluded that B. subtilis biopreparations can be used as growth promoters in chickens. Key words: probiotic, Bacillus subtilis, chickens, growth promoters